(untitled) (diségno, 2022)
It is now well known that digital production has almost completely supplanted the traditional drawing practices in the architectural process. If on the one hand the use of digital representation has interrupted traditional graphic production, on the other, it makes possible an increasingly effective and immersive dissemination of ancient architectural projects that are not sufficiently known, if not unpublished or, still, imagined. In this sense, this contribution aims to investigate and develop the digitization of one of the most important coastal projects put in place by the Ministry of Public Works and concretized through the drafting of the Album dei fari illustrato dalle notizie intorno ai loro caratteri e posizione, in order to make all those projects fully or partially realized for the growth of our coasts usable. The project proposed in 1873, the day after the unification of Italy, provides for the design and construction of four hundred and sixty-two maritime signals for the eight thousand kilometers of the Italian coast. The digitization of the Album dei fari, that is a cornerstone for the history of the construction of these coastal architectures, is therefore configured as the fundamental action to undertake a path of knowledge and digital comparison of past and present coastal structures, according to the dictates interdisciplinarity [Albisinni, De Carlo 2011].